Determinação simultânea de íons metálicos por meio de técnicas eletroanalíticas e quimiométricas - Farias, Marco Antonio dos Santos (Universidade Federal de São Carlos, 2011)
In this work, the determination of three metallic ions was performed, namely Zn2+, Cd2+ and Pb2+, in very different concentration range, from _g/L until mg/L, using differential pulse anodic stripping voltammetry over Carbon Fiber electrode where a Mercury film was deposited. Initially a factorial design of 23 was built where all possible combination among the ion concentrations were contemplated and in this way all interactions among the metallic ions were measured. The voltammetric curve was mean centered before the chemometric analysis. After that, the data were analysed using Partial Least Squares in the Principal Components domain was the used to quantify the ion concentration. The data treatment has been validated using cross and external validation methods. The final results showed low precision in the validation compared to those methods commonly used in the literature. After the chemometric treatment realized at first group of samples, two more groups in an extended concentration range, were built and tested using the same methodology. In these cases, again, the data validation lead to a low precision for practical application. It is important to emphasize that the low precision in the validation does not mean a chemotric approach to analyse electroanalytical data is not adequate, instead it means that among those chemometric technique, in the dissertation, we chose an inadequate one.
Simultaneous determinations of metallic ions using Eletroanalytical techniques and chemometric tools.
Keywords: Físico-química; Voltametria; Calibração multivariada; CIENCIAS EXATAS E DA TERRA::QUIMICA